PEMAHAMAN DAN PENGHAYATAN MAHASISWA STKIP WIDYA YUWANA TERHADAP VISI, MISI DAN TUJUAN STKIP WIDYA YUWANA - Silviana Elisken; Ola Rongan Wilhemus (Bahasa Indonesia, 2019)
College of Teacher Training and Education (STKIP) Widya Yuwana Madiun is an educational institution that forms Catholic Catechists and Teachers. College students are educated and nurtured to become candidates for catechists and religion teachers in accordance with the Vision and Mission of "Superior and Contextual". Research in this scientific work uses quantitative research methods. Research data is collected and analyzed quantitatively or statistically. The study was conducted on November 15, 2018 (preliminary study) and March 18-22 2019 (questionnaire test) on the campus of STKIP Widya Yuwana. Data collection is done by sharing questionnaires to be filled by college students. Respondent samples in this study amounted to 132 (one hundred thirty two) respondents consisting of 54 (fifty four) men and 78 (seventy eight) women. The technique of selecting respondents used a simple random sampling technique. The results of research data analysis on understanding and apreciation of Vision, Mission and Objectives of STKIP Widya Yuwana revealed that out of 132 (one hundred thirty two) respondents, 114 (86.4%) respondents stated that they were very understanding and live the vision and mission, and 17 (12.9%) the respondents stated that they understood and lived the Vision, Mission and Objectives of STKIP Widya Yuwana. Based on the results of the study, it can be concluded that, the majority of respondents understand and appreciate well the vision, mission and objectives of STKIP Widya Yuwana. The presentation of the results of the college students' understanding and appreciation of the vision, mission and objectives of the STKIP Widya Yuwana Campus can be improved through socialization at each campus activity.